Experimental study on the effect of ion transmission mode on the calcium leaching rate of cementitious materials - Shihao An; Chunmeng Jiang; Shuangxi Li; Chong Shi (Case Studies in Construction Materials)
The long-term calcium leaching in hydraulic concrete causes the dissolution of its internal calcifications, resulting in the formation of a porous and loose cement structure. Aggregates play a significant role in the erosion resistance of cementitious materials. Therefore, it is crucial to explore the influence of aggregates on the immersion of erosion media and the dissolution of calcium ions from concrete structures during the leaching process. In this study, concrete, mortar, and cement paste specimens with the same water–cement ratio were subjected to a complete immersion test in 6 mol/L ammonium chloride solution. The mass loss rate, leaching depth, and compressive strength loss rate of the three cement specimen types were specifically measured. In addition, XRD, MIP, and SEM assessments were used to observe and analyze the changes in the phase composition, pore structure, and microscopic morphology of the various types of specimens before and after calcium leaching. The time-varying behavior and damage mechanisms of the specimens of cementitious material systems with different aggregate compositions under the action of calcium leaching were investigated using macroscopic indexes with microscopic tests. Subsequently, the corrosion resistance performance of the concrete, mortar, and cement paste was compared and analyzed. The results demonstrated that under identical hydration processes, the porosity of concrete was reduced by 60.02 % compared to cement paste, while mortar achieved a reduction of 35.46 %. After accelerated erosion, the mass loss rates for concrete, mortar, and cement paste were 0.3 %, 1.46 %, and 1.89 %, respectively. Corresponding compressive strength loss rates were 20.33 %, 22.89 %, and 25.68 %, while leaching depths increased by 7.52 mm, 9.68 mm, and 11.65 mm, respectively. This indicated that aggregates in the cementitious material system effectively reduce porosity, improve packing density, and significantly limit ion transport during calcium leaching, thereby enhancing the material's resistance to calcium leaching. Furthermore, analyses of mechanical properties, phase composition, and pore structure evolution revealed that the benefits of improved erosion resistance from aggregates greatly surpassed the drawbacks of the interfacial transition zone.